Transient Cholestasis in Newborn Infants with Perinatal Asphyxia - D Herzog; P Chessex; S Martin; F Alvarez (Canadian Journal of Gastroenterology)
In asphyxiated newborn infants, cholestasis often leads to extensive investigations and a cause can rarely be found.